RENCANA PENDIRIAN BISNIS BARU “ROY SELF STIRRING MUG” - Roimondus Sanjaya Adi Nugroho; Anton Wuisan (Prosiding Working Papers Series In Management, 2018)
Roy Self Stirring Mug is a new business plan about innovation in mug glass. Roy Self Stirring Mug produce automatic stirrer in the stainless steel mug. Roy Self Stirring Mug promote it products by online, and has no fixed place. This products addressed to those who need practical product to support their daily acitivites. Its few competitors and similar products make the owner to start this business. The calculations of Net Present Value for five years is Rp 539.274.729,00 and the result is postitive make this business worth it to run. Keywords- self stirring, self stirring mug, stirrer, mug